Monoterpenol Oxidative Metabolism: Role in Plant Adaptation and Potential Applications - Ilc, Tina; Parage, Claire; Boachon, Benoît; Navrot, Nicolas; Werck-Reichhart, Danièle (Frontiers in Plant Science, 2016)
Plants use monoterpenols as building blocks for the production of functionally and structurally diverse molecules, which are key players in interactions with other organisms such as pollinators, flower visitors, herbivores, fungal or microbial pathogens. For humans, many of these monoterpenol derivatives are economically important because of their pharmaceutical, nutraceutical, flavor or fragrance applications. The biosynthesis of these derivatives is to a large extent catalyzed by enzymes from the cytochrome P450 superfamily. Here we review the knowledge on monoterpenol oxidative metabolism in plants with special focus on recent elucidations of oxidation steps leading to diverse linalool and geraniol derivatives. We evaluate the common features between oxidation pathways of these two monoterpenols, such as involvement of the CYP76 family, and highlight the differences. Finally, we discuss the missing steps and other open questions in the biosynthesis of oxygenated monoterpenol derivatives.